Plant hypersensitive response vs pathogen ingression: Death of few gives life to others. (August 2020) - Noman, Ali; Aqeel, Muhammad; Qari, Sameer Hasan; Al Surhanee, Ameena A.; Yasin, Ghulam; Alamri, Saad; Hashem, Mohamed; M Al-Saadi, Abdullah
Abstract: The hypersensitive response (HR) is a defense action against pathogen ingression. Typically, HR is predictable with the appearance of the dead, brown cells along with visible lesions. Although death during HR can be limited to the cells in direct contact with pathogens, yet cell death can also spread away from the infection site. The variety in morphologies of plant cell death proposes involvement of different pathways for triggering HR. It is considered that, despite the differences, HR in plants performs the resembling functions like that of animal programmed cell death (PCD) for confining pathogen progression. HR, in fact, crucially initiates systemic signals for activation of defense in distal plant parts that ultimately results in systemic acquired resistance (SAR). Therefore, HR can be separated from other local immune actions/responses at the infection site. HR comprises of serial events inclusive of transcriptional reprograming, Ca 2+ influx, oxidative bursts and phyto-hormonal signaling. Although a lot of work has been done on HR in plants but many questions regarding mechanisms and consequences of HRs remain unaddressed.We have summarized the mechanistic roles and cellular events of plant cells during HR in defense regulation. Roles of different genes during HR have been discussed to clarify genetic control of HR in plants. Generally existing ambiguities about HR and programmed cell death at the reader level has been addressed. Highlights: Plant resistance to attacking pathogens is escorted by the fast and multilayered defense responses. These defense response can be specifically or nonspecifically induced by multiple types of biotic or abiotic elicitors. HR in plants performs key functions for confining pathogen progression. HR activates defense in distal plant parts to initiate systemic acquired resistance (SAR). Pathogen Associated Molecular Patterns (PAMPs) is the prime tier of the plant innate immunity.